Analisis Penggunaan Sistem Pendaftaran Online (E-Health) berdasarkan Unified Theory of Acceptance and Use of Technology (UTAUT) - Nurus Sa’idah (Universitas Airlangga, 2017)
Surabaya is a pioneer of E-Health innovation in Indonesia by providing online registration system to facilitate to take a quenue number anytime anywhere. The users online registration at RSUD dr.M. Soewandhie Surabaya is the largest, but dissatisfaction figure of online registration services reached 31,4%. Therefore, the purpose of this research is to analyze use behavior online registration at RSUD dr.M. Soewandhie based on Unified Theory of Acceptance and Use of Technology (UTAUT). This research was an analytic observational with quantitative approach and cross sectional design. Sample were collected by systematic random sampling and consist of 50 users and 50 nonusers. The result showed that individual characteristic which has p value below 0,05 was experience, knowledge and IT skills. Performance expectancy (p = 0,044) significantly influence behavioral intention , whereas effort expectancy (p = 0,982) and social influence (p = 0,124) do not. Facilitating condition (p = 0,812) and behavioral intention (p=0,189) had no influence with use behavior because p value was above 0,05. In conclusion, performance expectancy has a significant influence with behavioral intention, therefore experience, knowledge and IT skills had influence with use behavior online registration in RSUD dr.M. Soewandhie Surabaya. Keyword: e-Health, online registration, Unified Theory of Acceptance and Use of Technology (UTAUT), use behavior